CREATING MARKETING KNOWLEDGE ABOUT THE CONSUMER IN THE CONTEXT OF THE DEVELOPMENT OF INTERNET TOOLS - MAZUREK-ŁOPACIŃSKA, Krystyna; SOBOCIŃSKA, Magdalena (Applied Computer Science, 2017)
The aim of the article is to present marketing knowledge about the consumer as an enterprise resource and the role of marketing research in expanding it in the context of progressive virtualization of social life and the development of Internet tools. The current article was written on the basis of an in-depth literature study and an analysis of the selected results of quantitative research conducted in 2013 on a sample of 152 enterprises.